Professional Linux programming - Masters, Jon (Wiley, 2007)
Describes the different development environments within Linux, including the kernal, the Web, and the desktop, and ways to integrate applications with the operating system.
Includes index
Keywords: Linux; Systèmes d'exploitation (Ordinateurs); Operating systems (Computers); Programmierung; LINUX